Mainstreaming zero carbon: lessons for built-environment education and training. Issue 1 (4th November 2020) - Stevenson, Fionn; Kwok, Alison
Highlights   Education and training are identified as a key means of reducing carbon emissions from buildings to help address the climate emergency. Institutional, industry and organisational responses are shown to be failing in this regard. This editorial introduces the themes and individual papers in the special issue and then explores the current state of the art through pedagogy, theory, training, policy, practice and standards. These areas are interrogated through three fundamental questions. How can education and training be rapidly changed to ensure the creation of zero-carbon built environments? How can this transition be implemented successfully? What positive examples and models can be drawn upon or adapted? In proposing an agenda for change, a new approach to education is set out which combines learning outcomes with new standards and personal values within a continual questioning and holding to account of all stakeholders involved through evidenced outcomes. This draws on evidence from the special issue and Capability Theory which allies competency with personhood to create capability through agency. The process to make this change requires: (1) government intervention, to ensure that the lowest common denominator is zero-carbon best practice within a negotiated, holistic approach to developing the built environment sustainably; (2) new ethical, interdisciplinary and collective educational working practices underpinned by new pedagogical theory and accreditation processes; and (3) rapid auditing and upskilling in climate literacy to bring pressure to bear on governments and institutions to carry out reforms.